Cost-effectiveness of primary offer of IVF vs. primary offer of IUI followed by IVF (for IUI failures) in couples with unexplained or mild male factor subfertility - Lyratzopoulos Georgios; Pashayan Nora; Mathur Raj (BMC, 2006)
Abstract Background In unexplained and mild male factor subfertility, both intrauterine insemination (IUI) and in-vitro fertilisation (IVF) are indicated as first line treatments. Because the success rate of IUI is low, many couples failing IUI subsequently require IVF treatment. In practice, it is therefore important to examine the comparative outcomes (live birth-producing pregnancy), costs, and cost-effectiveness of primary offer of IVF, compared with primary offer of IUI followed by IVF for couples failing IUI. Methods Mathematical modelling was used to estimate comparative clinical and cost effectiveness of either primary offer of one full IVF cycle (including frozen cycles when applicable) or "IUI + IVF" (defined as primary IUI followed by IVF for IUI failures) to a hypothetical cohort of subfertile couples who are eligible for both treatment strategies. Data used in calculations were derived from the published peer-reviewed literature as well as activity data of local infertility units. Results Cost-effectiveness ratios for IVF, "unstimulated-IUI (U-IUI) + IVF", and "stimulated IUI (S-IUI) + IVF" were £12,600, £13,100 and £15,100 per live birth-producing pregnancy respectively. For a hypothetical cohort of 100 couples with unexplained or mild male factor subfertility, compared with primary offer of IVF, 6 cycles of "U-IUI + IVF" or of "S-IUI + IVF" would cost an additional £174,200 and £438,000, representing an opportunity cost of 54 and 136 additional IVF cycles and 14 to 35 live birth-producing pregnancies respectively. Conclusion For couples with unexplained and mild male factor subfertility, primary offer of a full IVF cycle is less costly and more cost-effective than providing IUI (of any modality) followed by IVF.